Immobilizing Polar Bears/Inuit: Productivity and Interspecies Wildlife Management in the Canadian Arctic - Schreiber, Dorothee (Anthropologica, 2013)
In this article, I describe polar bear research in the Northwest Territories in the 1970s and 1980s. This research operated through understandings of biological productivity that biologists used to civilize Arctic environments. Wildlife biolo gists saw inefficiency, instability and waste in polar bears' fluc tuating fat stores. The Inuit hunt was similarly scrutinized for its conversion of polar bears into cash and its management of energetic resources. With the body as the locus of their concern, scientists monitored the circulation of energy in and between individuals and populations and, in doing so, demarcated the limits of normal biological function for both humans and bears.